Immune effector cell associated neurotoxicity syndrome in chimeric antigen receptor-T cell therapy - Sterner, Robert C.; Sterner, Rosalie M. (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-T cell therapy is an emerging staple in the treatment of certain hematological malignancies. While CAR-T cells have produced robust responses in certain hematological malignancies, toxicities associated with the therapy have limited their use. Immune Effector Cell Associated Neurotoxicity Syndrome (ICANS) is a potentially life-threatening neurotoxicity that commonly occurs with CAR-T cell therapy. Here we will discuss ICANS, its treatment, possible mechanisms, and potential solutions to this critical limitation of CAR-T cell therapy. As the field of CAR-T cell therapy evolves, improved treatments and methods to circumvent or overcome ICANS are necessary to improve morbidity, mortality, and decrease the cost of CAR-T cell therapy. This serious, life-threatening side effect needs to be studied to better understand its mechanisms and develop treatments and alternative strategies.